The Effects of Public Reporting on Physical Restraints and Antipsychotic Use in Nursing Home Residents with Severe Cognitive Impairment. Issue 3 (11th March 2014) - Konetzka, R. Tamara; Brauner, Daniel J.; Shega, Joseph; Werner, Rachel M.
<x xml:space="preserve">Abstract</x> Objectives To assess whether reductions in physical restraint use associated with quality reporting may have had the unintended consequence of increasing antipsychotic use in nursing home (NH) residents with severe cognitive impairment. Design Retrospective analysis of NH clinical assessment data from 1999 to 2008 comparing NHs subject to public reporting of physical restraints with nonreporting NHs. Setting Medicare‐ and Medicaid‐certified NHs in the United States. Participants Observations (N = 3.9 million) on 809, 645 residents with severe cognitive impairment in 4, 258 NHs in six states. Intervention Public reporting of physical restraint use rates. Measurements Use of physical restraints and antipsychotic medications. Results Physical restraint use declined significantly from 1999 to 2008 in NH residents with severe cognitive impairment. The decline was larger in NHs that were subject to reporting of restraints than in those that were not (–8.3 vs –3.3 percentage points, P < .001). Correspondingly, antipsychotic use in the same residents increased more in NHs that were subject to public reporting (4.5 vs 2.9 percentage points, P < .001). Approximately 36% of the increase in antipsychotic use may be attributable to public reporting of physical restraints. Conclusion This analysis suggests that public reporting of physical restraint use had the unintended consequence of increasing use of antipsychotics in NH residents with severe cognitive impairment.